Direct Transport to a Percutaneous Cardiac Intervention Center and Outcomes in Patients With Out-of-Hospital Cardiac Arrest. Issue 6 (June 2017) - Kragholm, Kristian; Malta Hansen, Carolina; Dupre, Matthew E.; Xian, Ying; Strauss, Benjamin; Tyson, Clark; Monk, Lisa; Corbett, Claire; Fordyce, Christopher B.; Pearson, David A.; Fosbøl, Emil L.; Jollis, James G.; et al.
Abstract : Background—: Practice guidelines recommend regional systems of care for out-of-hospital cardiac arrest. However, whether emergency medical services should bypass nonpercutaneous cardiac intervention (non-PCI) facilities and transport out-of-hospital cardiac arrest patients directly to PCI centers despite longer transport time remains unknown. Methods and Results—: Using the Cardiac Arrest Registry to Enhance Survival with geocoding of arrest location, we identified out-of-hospital cardiac arrest patients with prehospital return of spontaneous circulation and evaluated the association between direct transport to a PCI center and outcomes in North Carolina during 2012 to 2014. Destination hospital was classified according to PCI center status (catheterization laboratory immediately accessible 24/7). Inverse probability-weighted logistic regression accounting for age, sex, emergency medical services response time, clustering of county, transport time to nearest PCI center, initial heart rhythm, and prehospital ECG information was performed. Of 1507 patients with prehospital return of spontaneous circulation, 1359 (90.2%) were transported to PCI centers, of whom 873 (57.9%) bypassed the nearest non-PCI hospital and 148 (9.8%) were transported to non-PCI hospitals. Discharge survival was higher among those transported to PCI centers (33.5% versus 14.6%; adjusted odds ratio, 2.47; 95% confidence interval, 2.08–2.92). Compared with patients taken to non-PCI hospitals, odds of survival were higher for patients taken to the nearest hospital with PCI center status (odds ratio, 3.07; 95% confidence interval, 1.90–4.97) and for patients bypassing closer hospitals to PCI centers (odds ratio, 3.02; 95% confidence interval, 2.01–4.53). Adjusted survival remained significantly better across transport times of 1 to 5, 6 to 10, 11 to 20, 21 to 30, and >30 minutes. Conclusions—: Direct transport to a PCI center is associated with better outcomes for out-of-hospital cardiac arrest patients, even when bypassing nearest hospital and regardless of transport time. Abstract : Supplemental Digital Content is available in the text.